Minha história minha vida: percalços da formação em pedagogia - Santos, Enison Miquiles dos (Brasil, 2024)
This memoir aims to narrate my journey as a student and teacher. The written story first presents my origins, my people, and the challenges I faced to study, leaving my community for the city. The second part depicts leaving my parents' home in search of a better life and opportunities, as well as the beginning of my career as a substitute and later as a teacher in my community. The PIRAYAWARA PROJECT course and the Pedagogy course guided me to gain more experience as an educator in early childhood and elementary education. The activities developed in this setting were a great challenge. Finally, I will share a bit about my life both within and outside the profession. The methodology used was qualitative research, with data collection, opting for a narrative with an emphasis on life history. We consider that by recalling the events, each important moment shapes who we are and who I was in society. We learn and relearn, we are unfinished, and as we influence, we are also influenced.